Zambia : Country Procurement Assessment Report, Volume 1. Main Report - World Bank (Washington, DC, 2013)
The legal framework lacks robustness, and features structural and content inadequacies. Two current practices foster corruption and higher prices: using negotiations as an accepted procurement method, and, misusing the registration system for purchases from short-listed firms. Furthermore, procurement management is weak, showing incomplete procurement files, producing therefore avoidable losses for the government, while inadequacies in budget allocation, and in the funds release system reveal significant release delays, seriously affecting project implementation and contract management. Within this context, it is recommended to establish a procurement reform task force to initiate, and oversee the implementation set in the action plan developed by this CPAR. Moreover, the policy, and supervisory role of the Zambia National Tender Board (ZNTB) should be established, even prior to the new procurement legislation. The plan for a complete delegation of procurement authority should be finalized within a phased three-year period, and a professional procurement cadre should be established, defining its composition, with measures to support the management function. Other recommendations include the re-design of a registration list system, implementation of anti-corruption actions, and, introduction of appropriate procurement planning, and a new filing system.